Assessment of Primary School Teachers’ Knowledge regarding Child abuse in Kirkuk city Hewa - Hewa Star Salih (مجلة الموصل للتمريض, 2015)
Background and objective: Child abuse is most often due to the problems besetting families, which can elevate the risks to children. These problems are complex and interconnected, and require coordinated, holistic responses. Child abuse and neglect has begun to demonstrate linkages between maltreatment and long-term adverse effects and other social problems. The purpose of this study was to assess the Primary School Teacher Knowledge‘s Regarding Child Abuse In Kirkuk City" and find out the relationship between Teacher Knowledge‘s and some socio-demographic characteristic Material and Method: A descriptive study was carried out from July 2013 to April 2014. Data are collected through using the constructed questionnaire for the purpose of the study with the use of interview technique. Simple probability random sample of (100) science, manger and physical sport teachers is selected from (34) primary schools in Kirkuk city. A questionnaire is designed of (44) items for data collection, Data are analyzed through the application of the descriptive statistical analysis approach and inferential statistical approach. Frequencies, Percentage, men of score and chi-square. Results: The findings of the study indicated that majority of the teachers were between age (40-49 ) years and constitute (44.0% ) , (54 .0%) from teachers were female ,(54.0% )were graduate from Institute and (82.0%) from them were married . Conclusion: The result of the study find that overall depicts assessment are significant difference between teacher's knowledge and their some demographic data. Recommendations: The study recommended educational program should be designed to increase people knowledge and awareness about their child abuse. Striking up the center to solve the child's problem. Providing scientific booklet, publication and journal about child abuse and Providing the special law to protect the child for abuses. Keywords: Assessment, Primary School Teachers, Knowledge, Child abuse